Remote Sensing of Land Surface Phenology: Editorial - Ma, Xuanlong; Jin, Jiaxin; Zhu, Xiaolin; Zhou, Yuke; Xie, Qiaoyun (Remote sensing (Basel, Switzerland), 2022)
Land surface phenology (LSP) is an important research field in terrestrial remote sensing and has become an indispensable approach in global change research, as evidenced by many important scientific findings supported by LSP in recent decades [...]